2015
DOI: 10.1159/000441814
|View full text |Cite
|
Sign up to set email alerts
|

The Sustained-Exposure Dexamethasone Formulation OTO-104 Offers Effective Protection against Noise-Induced Hearing Loss

Abstract: The otoprotective effects of OTO-104 were investigated both prior to and following acute acoustic trauma. Guinea pigs received a single intratympanic injection of OTO-104 and were assessed in a model of acute acoustic trauma. Doses of at least 2.0% OTO-104 offered significant protection against hearing loss induced by noise exposure when administered 1 day prior to trauma and up to 3 days thereafter. Otoprotection remained effective even with higher degrees of trauma. In contrast, the administration of a dexam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…Similarly, it was found that an anti-IL-6-receptor antibody protected mice from NRHL (Wakabayashi et al, 2010). The anti-inflammatory and pro-resolution glucocorticoid dexamethasone (DEXA), delivered to the round window membrane, has also been shown to reduce hearing loss in patients after noise exposure (Zhou et al, 2013; Harrop-Jones et al, 2016). …”
Section: The Inflammatory Response and Its Resolutionmentioning
confidence: 99%
“…Similarly, it was found that an anti-IL-6-receptor antibody protected mice from NRHL (Wakabayashi et al, 2010). The anti-inflammatory and pro-resolution glucocorticoid dexamethasone (DEXA), delivered to the round window membrane, has also been shown to reduce hearing loss in patients after noise exposure (Zhou et al, 2013; Harrop-Jones et al, 2016). …”
Section: The Inflammatory Response and Its Resolutionmentioning
confidence: 99%
“…We opted for the use of a 6% Dex hydrogel, because such hydrogels have been reported to be well tolerated and effective drug delivery systems for the treatment of noise-induced hearing loss and cisplatin ototoxicity in guinea pigs Harrop-Jones et al, 2016;Piu et al, 2011]. TAAC concentrations of 6 and 30% were chosen to allow both, the comparison of hydrogels with a comparable glucocorticoid concentration and of glucocorticoid doses which are comparable according to their systemic efficacy .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in future studies the use of very high intratympanic glucocorticoid concentrations should be critically evaluated with respect to its risk-benefit ratio. The timing of glucocorticoid therapy emerged as important factor for its efficacy in various publications [Chang et al, 2009;Harrop-Jones et al, 2016;Honeder et al, 2016]. Glucocorticoid treatment before the actual insult to the inner ear results in better otoprotection in different trauma models including cochlear implantation and noiseinduced hearing loss Honeder et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations